“The school book question is a farce”: Free Textbook Provision in Nova Scotia, 1864-1944 - Clark, Penny; Gemmell, K.M. (Acadiensis, 2017)
Nova Scotia’s delayed introduction of a free school textbook policy until 1935 occurred without public debate – despite objections from booksellers and parental concerns about the spread of contagious diseases – and was due to three reasons: the strong opposition of Superintendent of Education Henry F. Munro, the state of the province’s economy, and the absence of advocacy on the part of lobby groups or members of the public. In the end, it was Liberal Premier Angus L. Macdonald, who, in spite of challenges, acted on a campaign promise to make textbooks free for all students in grades 1 to 8.